Área rural e urbana: estudo sobre qualidade de vida e nível de atividade física de idosos de Pimenta Bueno RO - Barbosa, Anderson Pedroso (2013)
Brazil is the fifth largest country in the world in extension and in its territory most places are conducive to agriculture, so the country has the field as one of its main income. With increased technology, however, the amount of labor from agriculture declined because the machines do most of the work of farmers, this technological advancement has made Brazil the increase and improve the quality of the grain produced in its territory. The residents of rural areas, especially elderly generally not accompanied these advances, making their income decrease and migrate to urban areas in search of better financial opportunities and structural, such as schools, hospitals, leisure and others. Based on this principle, this study aimed to know, what are the benefits and harms of migration of the elderly segment, for it used two questionnaires: WHOQOL - BRIEF able to verify the quality of life of respondents across four domains, which are: physical , psychological, environmental and social relations. The other questionnaire was the IPAQ - Long Version which aims to assess the level of physical activity of respondents, and divide them into work activities, domestic transportation and leisure. To know which would be the best places to live, ensuring better quality of life were interviewed 40 individuals, 20 of rural residents and 20 residents of the urban area to the location of the elderly was requested, help desk assistant social pepper - Bueno - RO, municipality of research. The formation of the group of respondents was random